The X Files: “The Mystery of X Chromosome Instability in Alzheimer’s Disease” - Bajic, Vladan P.; Essack, Magbubah; Zivkovic, Lada; Stewart, Alan; Zafirovic, Sonja; Bajic, Vladimir B.; Gojobori, Takashi; Isenovic, Esma; Spremo-Potparevic, Biljana (Frontiers in Genetics, 2020)
Many years have passed from the discovery that a genetic component on chromosome 21 is the fundamental cause of early-onset, but also to the late onset of Alzheimer’s disease (LOAD). In the genetic sense, only the apolipoprotein E4 gene is found to be a risk factor for LOAD. Genetic risk assessment has not changed fundamentally in recent years despite the hypothesis that many additional unidentified genes are likely playing a role in AD development. In this review, we elaborate the role of X chromosome epigenetics in the controversial findings from genome-wide association studies of the protocadherin 11 gene and hypothesize that the other genetic risk factors may be based on X-chromosome epigenetics in AD.